Neuropathological Developments in Sudden Infant Death Syndrome. (November 2018) - Bright, Fiona M; Vink, Robert; Byard, Roger W
A wide variety of neuropathological abnormalities have been investigated in infants who have died of sudden infant death syndrome (SIDS). Issues which detracted from early studies included failure to use uniform definitions of SIDS and lack of appropriately matched control populations. Development of the triple risk model focused attention on the concept of an inherent susceptibility to unexpected death in certain infants, with research demonstrating a role for the neurotransmitter serotonin within the brainstem. However, it now appears that neuropathological abnormalities in SIDS infants are more complex than a simple serotonergic deficiency in certain medullary nuclei but instead could involve failure of an integrated network of neurochemical transmitters in a variety of subcortical locations. The following overview examines recent research developments looking particularly at the potential role of the peptide neurotransmitter substance P and its neurokinin-1 receptor in multiple nuclei within the brainstem, asymmetry and microdysgenesis of the hippocampus, and decreased orexin levels within dorsomedial, perifornical, and lateral levels in the hypothalamus. Whether such research will lead to identifiable biomarker for infants at risk of SIDS is yet to be established. Use of standardized and consistent methods of classifying and categorizing infant deaths will be pivotal in generating reproducible research results.